Sharia financial in cross civilization and humanity: a study of alternative solutions to the economy - Nur Baiti, Septi Vivia; Firgianti, Shovia Indah; Nugraha, Ahmad Lukman (Journal of Islamic Economics Management and Business (JIEMB), 2021)
Ribā is a global humanitarian problem, so it negatively impacts human life. Therefore, the non-ribawī system built by Islam can be an alternative to the global and national financial systems.This research aims to explore the implementation of the sharia system as an alternative or solution to the financial system in Indonesia and its impacts. This research uses a descriptive qualitative approach with secondary data sources, namely official documents on Islamic economics and official documents of Islamic banks. The results of this study indicate that one of the implementations of the Islamic economy is through Islamic banking. Islamic banking can be an alternative solution to the economic system in Indonesia. In addition, the application of Islamic economics has a reasonably broad impact on society, one of which is that Islamic economics can reduce economic vulnerability due to a decoupling economy phenomenon. Through a profit-sharing system, the Islamic economy makes no distance between the financial and real sectors. This research has implications for efforts to avoid speculative financing, financial market exploitation, and a social environment that only favours the economic interests of capital owners.